ANALISIS DAN PERANCANGAN SISTEM E-LEARNING BERBASIS WEB PADA SMA NEGERI 4 KOTA JAMBI - Hakim, Ibnu; Assegaff, Setiawan (LPPM Universitas Dinamika Bangsa, 2018)
E-Learning can be used as an alternative way in educational problems, whether as an addition, completion, or substitution of the teaching-learning process. It is very recommended for ICT (Information Communication and Technology)-based school. SMA Negeri 4 Jambi City has that kind of technology. It needs a new system called E-Learning. This system is made as a prototype which will be improved in the future. This prototype form of E-Learning system will be developed with facilities needed by the teachers, the students, and the school, such as sending files, showing videos, chatting, and quizzes. These facilities will encourage the students to learn. The writer expects that this prototype form of E-Learning system can help schools reach the educational goals of the country, Indonesia.